1986
DOI: 10.1177/002076408603200407
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Health Care Professionals towards Patients who Take Overdoses

Abstract: The attitudes of health care professionals in Malta towards patients who take drug overdoses were studied. It was found that the intention of the overdose had a marked effect on the attitude of the health care professional towards the patients. Differences between different professionals were noted and the Maltese results were compared with those of a similar study in London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Ghodse et al (1986) highlight unfavourable attitudes in medical and nursing staff to patients who overdose, and these are even worse when there is perceived alcohol or drug dependence. Measuring the attitudes of health professionals, Fleming & Szmukler (1992) found that patients with anorexia were seen as “less likeable” than other patients and as being responsible for their illness.…”
Section: The Psychiatric Literaturementioning
confidence: 99%
“…Ghodse et al (1986) highlight unfavourable attitudes in medical and nursing staff to patients who overdose, and these are even worse when there is perceived alcohol or drug dependence. Measuring the attitudes of health professionals, Fleming & Szmukler (1992) found that patients with anorexia were seen as “less likeable” than other patients and as being responsible for their illness.…”
Section: The Psychiatric Literaturementioning
confidence: 99%
“…The majority of research literature looking at staff attitudes towards DSH has taken place in medical settings such as Accident and Emergency (A&E) departments of general hospitals. Ghodse (1978) and Ghodse et al (1986) found that patients who had taken accidental overdoses were regarded more favourably than those who had taken deliberate overdoses, who in turn were viewed more positively than overdoses occurring through drug addiction. McAllister, Creedy, Moyle and Farrugia (2002) reported a generally negative attitude from emergency department staff towards clients who self-harmed, and a correlation was found between years of experience and an empathic approach towards clients.…”
Section: Introductionmentioning
confidence: 99%
“…This reveals the negative attitude towards the profession even by health professionals. [16][17][18][19][20] Psychiatrists are already in shortage in Pakistan and this attitude will bring negativity towards the profession itself. 47.9% of students considered using words like crazy for people with severe mental illnesses.…”
Section: Discussionmentioning
confidence: 99%